ENERGY RESOLUTION OF PLASTIC SCINTILLATOR FOR ELECTRON AND PROTON - VO , HONG HAI; RICOL, JEAN-STEPHAN; M. NOMACHI; Y. SUGAYA; K. YASUDA (Nuclear Science and Technology, 2011)
The aim of this work was to study the energy resolution of the plastic scintillator (i.e. organic solid scintillator) for electron and proton particles. Recent works have shown that the energy resolution consists of not only the statistical uncertainty, but also an “excess” fluctuation. The behavior of the excess fluctuation was known as non-statistical fluctuation, which arises mainly as the intrinsic energy resolution. In this work, the energy resolution was analyzed in separated components (statistic uncertainty and intrinsic energy resolution). We studied the energy resolution for electron and proton particle. In this work, we employed mono-energetic electron beams from the electron spectrometer at CENBG (Le Centre d’Études Nucléaires de Bordeaux Gradignan), France, and mono-energetic proton micro-beams at the Wakasa wan Energy Research Center (WERC), Japan. The 0.975-MeV conversion electron from a 207Bi radioisotope source was also used for energy calibration and comparison purposes with electron beam.